Evaluación de posturas de trabajo para el diseño de sillas y mesas ergonómicas en los departamentos de sindicatura, comunicación, turismo y talento humano del GAD de Guano - Ponce Sanabria, Nayely Dayana (2025)
This study evaluated work postures and designed an ergonomic furniture model for the departments of receivership, Communication, Tourism and Human talent of the GAD Guano using a detailed and technical approach. The Kuorinka Nordic questionnaire was used to diagnose musculoskeletal pain areas, identifying mainly conditions in the lumbar, cervical and shoulder regions. The evaluation of the workstations was carried out with the Rosa method and specific anthropometric measurements, ensuring optimal adequacy of the furniture and work equipment. The environmental assessment included noise measurements. Temperature and lighting, showing noise levels below 70 decibels, temperatures between 20 - 24 °C and lighting levels between 300 - 500 Lux, confirming the absence of significant physical risks. Based on the data collected, an ergonomic furniture proposal was developed that included height-adjustable desks and chairs with adjustable lumbar support. These elements were designed to promote correct posture and minimize the risk of musculoskeletal disorders. In conclusion, the study identified and addressed the main ergonomic risk factors in the departments evaluated, providing specific solutions that will significantly improve the working conditions and well-being of GAD Guano's employees, and the implementation of these recommendations will contribute to creating a safe, comfortable and productive work environment.